(untitled) (Damascus University Journal for engineering sciences, 2021)
These days, demanding for coal and minerals is steadily increasing in order to increase the productive capacity of enterprises and competition in global markets at the lowest cost. The provision of minerals is related to the extraction of large quantities of raw materials depending mainly on the effectiveness of machines operating in this regard. Therefore, mining industry is developing on a variety of machines that operate in different ways in this field, including impact drilling (shock) and this requires the improvement of drilling equipments in order to reduce labor, time, energy and money. The drilling machines of impact drilling (shock) depend mainly on several elements: the shocker and the drilling tool) the wave carrier formed by the shocker). When the wave carrier hits, a wave of deformation spreads at the speed of sound in the carrier’s metal and has specific parameters related to the shocker specifications where the wave the place energy is to be invested in destroying it. The shock and energy-loaded wave is transmitted through the wave carrier until it reaches its end, where part of this energy is utilized, one part is scattered in the surrounding middle, and another part reflects back to the machine without any benefit and therefore determines the yield or effectiveness of the machine operating on this principle. In order to take advantage of the greatest amount of energy carried in the wave, the designer must form a wave with specific parameters that almost match the specifications of the dynamic resistance of the material to be broken, this result in more efficient machine performance. It was found through research in the parameters of the elastic waves formed, that the main part of the wave, which has a specific continuity, who plays a main role in breaking the material. This research concludes to an important conclusion linking the main wave shape and the shocker shape and finding the appropriate and optimal design for the shocker compatible with the dynamic resistance of the material to be broken, without the need to change the machine’s capacity or specifications.